Effect of Mechanical Alloying Time on Microstructure, Hardness and Electrical Conductivity Properties of Cu-B4C Composites - Houssain, Hasaneen; Cengiz, Ahmet Oğuzhan; Islak, Serkan (Kastamonu University, 2024)
This study aims to investigate the effect of mechanical alloying time on the microstructure, hardness, and electrical conductivity properties of copper (Cu) matrix boron carbide (B4C) reinforced composites. Cu-B4C composites with 2% B4C by volume were subjected to mechanical alloying processes for 0, 1, 5, 10, and 20 hours. The microstructure and phase formation of the composites were examined using scanning electron microscopy (SEM) and X-ray diffraction (XRD). Hardness measurements of the composites were conducted using the microhardness measurement method, and density values were determined using the Archimedes principle. The electrical conductivity values of the samples were measured in terms of the international annealed copper standard (%IACS) based on the eddy current principle. SEM images revealed a more homogeneous distribution of B4C particles in the Cu matrix as the mechanical alloying time increased. Hardness values showed significant increases with the increasing mechanical alloying time, reaching the highest value in the 20 h milled sample with a 90.86 value. The effect on electrical conductivity values was noteworthy, with a measurement of 63% IACS at 0 hours and 25% IACS at 20 hours of mechanical alloying.
Keywords: Cu-B4C composites; mechanical alloying time; electrical conductivity; microstructure; hardness; Mechanical Engineering (Other); Makine Mühendisliği (Diğer)